(untitled) (Research, Society and Development, 2022)
SARS-CoV-2 (Severe Acute Respiratory Syndrome CoronaVirus) is the etiological agent responsible for the development of coronavirus disease (COVID-19). Which is a disease that affects the airways, and most often can cause pneumonia. Despite the viral origin, antimicrobial drugs are often prescribed, so that about 15% of patients with SARS-CoV-2 have a secondary infection caused by bacteria, which explains the antibiotic treatment. These drugs, when prescribed regardless of the existence of a bacterial infection, can lead to possible bacterial resistance. The objective of this work is to analyze the profile of laboratory tests of patients admitted to an ICU with severe forms of COVID-19, in a private hospital in a city in the southwestern region of Bahia. This is a documental study, with primary data source. The approach is quantitative, descriptive, exploratory, and cross-sectional, through data survey. Among the 52 medical records evaluated, it was possible to observe that the male gender had a higher rate of hospitalization and most of them were elderly. It is possible to observe an increase in the number of leukocytes and platelets after antibiotic therapy. And in relation to CRP, the value was significantly reduced after the administration of antimicrobial drugs. According to the analysis of the laboratory results, it was possible to observe that there were important alterations in the infection markers, which may be related to the use of antimicrobial drugs.